Conceptualizing the Science-Practice Interface: Lessons from a Collaborative Network on the Front-Line of Climate Change - Kettle, Nathan P.; Trainor, Sarah F.; Loring, Philip A. (Frontiers in Environmental Science, 2017)
The gap between science and practice is widely recognized as a major concern in the production and application of decision-relevant science. This research analyzed the roles and network connections of scientists, service providers, and decision makers engaged in climate science and adaptation practice in Alaska, where rapid climate change is already apparent. Our findings identify key actors as well as significant differences in the level of bonding ties between network members who perceive similarity in their social identities, bridging ties between network members across different social groups, and control of information across roles – all of which inform recommendations for adaptive capacity and the co-production of usable knowledge. We also find that some individuals engage in multiple roles in the network suggesting that conceptualizing science policy interactions with the traditional categories of science producers and consumers oversimplifies how experts engage with climate science, services, and decision making. Our research reinforces the notion that the development and application of knowledge is a networked phenomenon and highlights the importance of centralized individuals capable of playing multiple roles in their networks for effective translation of knowledge into action.